PERSEPSI MASYARAKAT MENGENAI KEBERADAAN PERTAMBANGAN MINYAK DAN GAS DI KECAMATAN SOKO DAN RENGEL, KABUPATEN TUBAN - Tama, Fahmi Amel Dwi; Fatimah, Endrawati; Yahya, Wisely (Jurnal Lingkungan dan Kota, 2023)
The existence of oil and gas mines in a region generally has both positive and negative impacts on the area. One of the oil and gas mines in East Java Province is located in Tuban Regency, specifically in the districts of Soko and Rengel, which have been operating for twenty-five years. The existence of the oil and gas mine is believed to affect various aspects. This study aims to identify the influence of the presence of oil and gas mining in the districts of Soko and Rengel based on the perceptions of the community. The method used in this study is a quantitative method with scoring analysis obtained from primary data in the form of a questionnaire from 99 respondents. The community assesses that the presence of oil and gas mining moderately affects the physical aspect, the environment, the health of the community, and the social aspect. On the other hand, the presence of oil and gas mining is not considered to have an impact on the economic aspect. This research contributes by providing a perspective that the presence of oil and gas mining in the districts of Soko and Rengel, Tuban Regency, is considered to have limited positive influence on the surrounding community.